Remodeling of Trunk and Backshape Deformities in Patients with Scoliosis Using Standardized Asymmetric CAD / CAM Braces - Weiss, Hans-Rudolf; Moramarco, Marc (Highlights on Medicine and Medical Research Vol. 11, 2021)
In literature, there are papers on scoliosis reporting improvements of spinal curvatures under brace treatment, but this predominately relates to results revealed on x-ray, not clinically. Therefore, it is worthwhile (1) to review the literature showing improvements after brace treatment and (2) to show what can be done conservatively via bracing in curvatures exceeding 45° Cobb. Materials and Methods: (1) A Pub Med review of the literature with a keyword search for (a) ‘scoliosis’, ’brace treatment’ and ‘improvement’ and alternatively for (b) ‘scoliosis’, ‘orthosis’ and ‘improvement’. (2) Additionally, a case series of patients is demonstrated with curvatures exceeding 45° clinically and radiologically. Results: 92 papers displayed in the keyword search for (a) ‘scoliosis’, ’brace treatment’ and ‘improvement’ and 79 papers displayed with the keyword search for (b) ‘scoliosis’, ‘orthosis’ and ‘improvement’. A case series of three patients with curvatures exceeding 45° is demonstrated within this paper revealing radiological and clinical improvement when using the recent Chêneau standard of bracing with a reliable CAD library of braces and an experienced team. Discussion: The solution for the high variability of bracing outcomes is standardization. Braces can be standardized when applying well-tested, standardized brace models from CAD libraries. In comparison, braces made manually cannot be standardized, resulting in unpredictable outcomes. In addition, there is future advancement potential of baseline quality in braces produced using CAD/CAM technologies. Conclusions: Trunk and backshape can be improved conservatively even in patients with curvatures exceeding 45°. Modern concepts of bracing may improve even scoliotic deformities exceeding 45° Cobb, radiologically. Clinical improvements, with modern bracing concepts, are comparable to clinical improvements via surgery. For the majority of scoliosis patients with curvatures exceeding 45°, surgery is not indicated considering the long-term detrimental effects as shown in literature.